Flipbook Literacy Narrative Local Wisdom Palembang Assisted by PQ4R Method in Reading Comprehension of Students - Nofa, Heny Puspita Dia; Purwati, Panca Dewi; Sabilillah, Nugraheti Sismulyasih (Journal of Education Reseach and Evaluation, 2025)
The low reading comprehension ability of fourth grade students in reading elements. Students have not determined the main idea and supporting ideas in narrative texts. This study aims to develop digital based learning media to improve the reading comprehension ability of high grade students. The research method is research and development (R&D) with the Borg and Gall model. The subjects of this study were material experts and learning media experts. The subjects of the product trial were teachers and 25 fourth grade students. The data collection methods were observation, interviews, questionnaires, documentation, and tests. The instruments used in collecting data were questionnaire sheets and test questions. The techniques used to analyze data were qualitative and quantitative descriptive analysis. The effectiveness of the media was based on the pretest and posttest scores of students tested using the N-Gain test. The results of the study were the feasibility of learning media through the assessment of media experts obtained a score of 92.59 (very feasible), and material experts obtained a score of 77.58 (feasible) with an average score of 85.08 (very feasible). The results of the media effectiveness test obtained data showing an increase in students' reading ability by 47.37 in the small group product trial and 50.04 in the large group product trial. The pretest value experienced an average increase (N-gain) of 0.81 with high criteria, and the posttest value experienced an average increase (N-gain) of 0.80 with high criteria. It was concluded that flipbook media is feasible and effective for improving the reading comprehension skills of grade IV students.